Effects of group living on pupation in a Lady Beetle - Gordon, Haley; Huston, Miranda; Arnold, Shara; Marshall, Jeremy; Michaud, J.P. (My University, 2018)
Lady beetles, sometimes also called ladybugs, are a species of insect with brightly-colored wing covers that are often a shade of red or orange with black spots (Michaud and Qureshi 2006). Lady beetles are generally a beneficial insect, as most of them are carnivorous and predators of aphids, scales and other juice-sucking plant parasites. In fact, one lady beetle can eat as many as 5,000 aphids over the course of its lifetime! Lady beetles are also widely studied in behavior, as they exhibit a range of social and antisocial behaviors (i.e., cannibalism). Here, we tested if lady beetle larvae reared in groups would exhibit different pupation development times relative to beetles reared alone. We found that group living resulted in greater synchronization of pupation development, likely due to an increase in the possibility of cannibalism. Further research is needed to test this hypothesis.
Keywords: Fall 2018